Evaluation of enamel surface roughness using different types of polishing system after orthodontic bracket debonding - Maryam Fouad Bilal; Lanja Abubakir Ali; Deman Hasan Hamid; Rebin Ali Mohammed Amin (Erbil Dental Journal)
Background: returning surface of the enamel to its pre-orthodontic state after debonding of brackets without any damage to the texture of enamel is a clinical contest. removal of Residual adhesive using correct and suitable tools and methods ensures a smooth surface and healthy plaque-free environment. Therefore; the study aims to determine the safest method to finish enamel surface after bracket debonding using three different methods. Method: Thirty premolars extracted for orthodontic purposes were selected for this study. The samples were coded 1-30 randomly and surface roughness was measured before bracket placement using profilometer. Then bracket bonded in the middle third of the buccal surface of the premolars and then debonded using debonding plier. The sample was divided into three groups, 10 for each group (group 1: 18-flute tungsten carbide bur, group 2: 12- flute tungsten carbide bur, group 3: adhesive removing plier). Then the second roughness measurement was recorded. Result: It is found that debonding with adhesive removing plier was the least efficient method followed by 12-fluted tungsten carbide bur, so the best clean-up method in this study achieved is by using 18-fluted tungsten carbide bur. Conclusion: The 18-fluted flame-shaped tungsten carbide bur at high speed for orthodontic adhesive removal demonstrated more favorable results in our hands, as it resulted in the smoothest enamel surface and could reasonably be used as a standard by which future other burs or other procedures are compared.